Jus Cogens : Redux - Sellers, Patricia Viseur (AJIL unbound, 2022)
In The Boundaries of International Law: A Feminist Critique ( Boundaries ) , 1 amidst observations about masculine bias in treaty law, co-authors Christine Chinkin and Hilary Charlesworth queried the masculine configuration, i.e., the gender of jus cogens or peremptory norms. A peremptory norm is “accepted and recognized by the international community . . . as a norm from which no derogation is permitted and which can be modified only by a subsequent norm of international law having the same character.” 2 Interrogating whether jus cogens privileged the experiences of males over that of females, they challenged jus cogens ’ presumed universality and its intended utility. Accepted peremptory norms, they averred, exerted a silencing, deleterious impact on core feminine values such as sexual equality or freedom from gender discrimination. 3 Decades after the Vienna Convention on the Law of Treaties’ (VCLT) codification of jus cogens , the International Law Commission (ILC) reified a non-exhaustive list of peremptory norms that explicitly excluded gender-based discrimination. 4 This essay proposes a “ jus cogens redux” to revive Chinkin and Charlesworth's question by peering at several threads in the thwarted conversations about whether freedom from gender discrimination rises to peremptory norm status. The conversational threads lay tattered by positive law's reliance on enumerated treaty provisions and accepted precepts of customary international law. They are frayed by normative law's philosophical, moralists’ approach. Neither the positivist law nor the normative law's concepts of how to determine jus cogens values grapples with gender or gender minorities. By default, each retains a masculine approach that configures the gender of jus cogens as “non-female.”